No breast cancer subgroup can be spared postoperative radiotherapy after breast-conserving surgery. Fifteen-year results from the Swedish Breast Cancer Group randomised trial, SweBCG 91 RT. (November 2016) - Killander, F.; Karlsson, P.; Anderson, H.; Mattsson, J.; Holmberg, E.; Lundstedt, D.; Holmberg, L.; Malmström, P.
Abstract: Background: Breast-conserving surgery (BCS) followed by radiotherapy (RT) is an established treatment for women with T1-2N0 breast cancers. Since subgroups of patients have low ipsilateral breast tumour recurrence (IBTR) rates, it is important to study whether RT is necessary for all patients. Patients and methods: A total of 1187 women with primary T1-2N0M0 breast cancer were randomised, after standardised sector resection, to postoperative whole breast RT or no local treatment. Adjuvant systemic therapy was offered to patients with stage II cancers. Patients were followed with clinical examinations and annual mammography for 10 years and thereafter referred to the Swedish mammography screening program. Results: After 15 years of follow-up, a higher cumulative incidence of IBTR was observed in control patients, 23.9%, versus irradiated patients, 11.5%, P  < 0.001. Recurrence-free survival was inferior, 51.7% versus 60.4%, P  = 0.0013. The main effect of RT was seen during the first 5 years. However, overall survival was not significantly lower 68.4% versus 71.1%, P  = 0.68, nor was breast cancer–specific mortality significantly higher. Conclusions: RT after BCS significantly reduced the incidence of IBTR at 15 years of follow-up. We were unable to identify subgroups which could be spared RT. Breast cancer mortality was not significantly reduced after RT. Good predictive markers for radiation sensitivity and improved adjuvant systemic therapy are needed to omit RT after BCS. Highlights: Radiotherapy after sector resection reduces ipsilateral breast tumour recurrences. Main effect of postoperative radiotherapy is seen within 5 years of breast surgery. All subgroups analysed in the study benefit from postoperative radiotherapy. Contralateral breast cancers are not uncommon as first events.